Effect of Moringa oleifera Leaf Extract on the Growth Performance, Hematology, Innate Immunity, and Disease Resistance of Nile Tilapia (Oreochromis niloticus) against Streptococcus agalactiae Biotype 2 - Manoj Tukaram Kamble; Wenresti Gallardo; Krishna Rugmini Salin; Suntree Pumpuang; Balasaheb Ramdas Chavan; Ram Chandra Bhujel; Seema Vijay Medhe; Aikkarach Kettawan; Kim D. Thompson; Nopadon Pirarat (Animals, 2024)
The present study aimed to investigate the effects of Moringa oleifera leaf (MLE) extract-supplemented diets on the growth, feed utilization, hematology, innate immune response, and disease resistance of Nile tilapia against Streptococcus agalactiae Biotype 2. Four hundred and fifty Nile tilapia (32.61 ± 0.2 g/fish) were randomly allocated into fifteen tanks (30 fish/tank). Different concentrations of MLE at 0%, 0.5%, 1%, 1.5%, and 2% were fed to the Nile tilapia for 30 days, and the growth, feed utilization, hematology, and innate immune response of the Nile tilapia were determined. After the feeding trial, the Nile tilapia were challenged with a S. agalactiae Biotype 2 infection, and the relative percentage of survival (RPS) was determined. Results revealed the presence of quercetin, kaempferol, and p-coumaric acid in the MLE extract, exhibiting stronger antimicrobial activity against S. agalactiae Biotype 2. The diets supplemented with the MLE-0.5 group showed a significantly higher growth, feed utilization, hematology, and innate immune response in the Nile tilapia compared to the control and other MLE groups. Additionally, the MLE-0.5 group exhibited a significantly higher RPS of the Nile tilapia against S. agalactiae Biotype 2. Therefore, MLE-0.5 can be employed as an alternative feed supplement in sustainable Nile tilapia farming to protect against S. agalactiae Biotype 2.